2016
DOI: 10.7589/2015-10-276
|View full text |Cite
|
Sign up to set email alerts
|

Chlamydia pecorum Infection in Free-ranging Koalas (Phascolarctos cinereus) on French Island, Victoria, Australia

Abstract: We detected Chlamydia pecorum in two koalas ( Phascolarctos cinereus ) from a closed island population in Victoria, Australia, previously free of Chlamydia infection. The ompA and multilocus sequence type were most closely related to published isolates of livestock rather than koala origin, suggesting potential cross-species transmission of C. pecorum .

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
41
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(43 citation statements)
references
References 14 publications
2
41
0
Order By: Relevance
“…The presence of genotype L in this population, not previously detected in koalas and not found in other Victorian populations in this study, suggests this C. pecorum strain was not moved with the koalas when this population was established by translocation of koalas from French Island in the 1980s (Martin, 1989). The origin of genotypes L, M and N in koalas is unknown, although their close similarity to C. pecorum ompA sequences from livestock raises interesting questions over the potential for cross-host transmission from livestock, for which molecular evidence continues to grow (Jelocnik et al, 2013;Bachmann et al, 2015;Legione et al, 2016). Future sampling of livestock that occupy ranges overlapping those of koala populations would be invaluable in investigating this hypothesis further.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The presence of genotype L in this population, not previously detected in koalas and not found in other Victorian populations in this study, suggests this C. pecorum strain was not moved with the koalas when this population was established by translocation of koalas from French Island in the 1980s (Martin, 1989). The origin of genotypes L, M and N in koalas is unknown, although their close similarity to C. pecorum ompA sequences from livestock raises interesting questions over the potential for cross-host transmission from livestock, for which molecular evidence continues to grow (Jelocnik et al, 2013;Bachmann et al, 2015;Legione et al, 2016). Future sampling of livestock that occupy ranges overlapping those of koala populations would be invaluable in investigating this hypothesis further.…”
Section: Discussionmentioning
confidence: 99%
“…These data were included to improve the power of our study and increase the likelihood of accurate correlations being described. For similar reasons, here we also include the clinical data from two Chlamydia-positive koalas from French Island, whose ompA genotypes we reported recently (Legione et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This observation was also repeated in the recent MLST of C. pecorum infecting koalas from French Island in Victoria. In this study, it was also observed that the certain koala strains were more similar to livestock strains than they were to other koala strains 17 Figure 1. Genetic relationships of C. pecorum strains found in various hosts.…”
Section: Pecorum Molecular Epidemiologymentioning
confidence: 66%